Synthesis and Crystal Structure of A Novel 1D Supramolecular Complex: [C21H18N6S2I2Hg]2?CH3OH - Dong, Hua-Ze; Bi, Wen-Tao; Zhu, Hai-Bin (Asian Journal of Chemistry, 2010)
A novel 1D supramolecular complex with a formula as [C21H18N6S2I2 Hg]2·CH3OH, was formed by the reaction of 1,3-bis(4-(pyridine-3-yl)- pyrimidine-2-ylthio)propane with HgI2, in which metal ion was in a four-coordinated environments with a distorted tetrahedral geometry. Then independent zigzag chains are linked each other and pack in 3Dsuperamolecular network via hydrogen bonds. The crystal is triclinic, space group P-1 with unit cell parameters: a = 11.1806(14) Å, b = 15.4729(19) Å, c = 16.875(2) Å, α = 75.028(2)º, β = 86.737(2)º, γ = 71.171(2)º, V = 2668.2(6) Å3, Z = 2, Mr = 1777.9, Dc = 2.213 g/cm3, μ = 8.263 mm-1, F(000) = 3078, R = 0.0428, wR = 0.0831 for 9220 reflections with I > 2σ(I).